Bordando con tinta negra: prensa y autoría femenina en la revista La Mujer Mexicana (1904-1908) - Ximena Yáñez Chávez; Ana Laura Zavala Díaz (Les Cahiers ALHIM)
In this article we are interested in studying the discursive strategies of authorial construction of the female writers who collaborated in the magazine La Mujer Mexicana (1904-1908), spokesperson of the Sociedad Protectora de la Mujer. If when speaking of authorship, we think of formats that put individual subjects on stage, the printed matter in which the signatures of more than one name are gathered —newspapers, magazines or anthologies— are, likewise, manufacturers of authorial, collective and collaborative symbolic capital. We share with Beatriz Sarlo the idea that periodicals are a starting point to investigate the institutional and social transformations that affect literary discourse; therefore, we believe that the review of this magazine allows us to approach the notions of “female writer” and “female writing” that circulated against the tide of the dominant Mexican culture of the early twentieth century.